A theoretical axial stress-strain model for circular concrete-filled-steel-tube columns. (15th October 2016) - Lai, M.H.; Ho, J.C.M.
Highlights: A new hoop strain equation for CFST column is developed based on 122 test results. A theoretical axial stress-strain model with complex 3D stress state is proposed. Applicability of the proposed model verified by 422 test results. The model to predict the behaviour of confined concrete is verified by test result. Abstract: Concrete-filled-steel-tube (CFST) columns are widely adopted in many structures nowadays attributed to the superior behaviour developed by the composite action. However, the composite action cannot be fully developed because of different dilation properties of steel tube and concrete in the elastic stage. Moreover, due to the inelastic outward buckling of steel tube, CFST columns may suffer serious degradation. To overcome these problems, external confinement, such as rings, ties, spirals and FRP wraps have been studied recently and proven experimentally to have potential in improving the uni-axial behaviour of CFST columns. In this paper, an experimental database containing 422 uni-axial compression test results of unconfined and externally confined CFST columns has been assembled. In addition, a theoretical model has been proposed for predicting the uni-axial behaviour of circular CFST columns. This model consists of mainly three components: (1) Constitutive model of confined concrete modified from Attard and Setunge's actively confined concrete model. (2) Constitutive model of steel tube under complex stress-state using Prandtl-Reuss theory. (3) The interaction among external confinement, steel tube and core concrete based on new a hoop strain equation. The validity of the proposed model has been verified by comparing the predicted results with the experimental database.